In utero exposure to di-(2-ethylhexyl) phthalate induces metabolic disorder and increases fat accumulation in visceral depots of C57BL/6J mice offspring - Gu, Hailun (Exp Ther Med, 2016)
Excessive visceral fat accumulation is associated with metabolic disorders. Di-(2-ethylhexyl) phthalate (DEHP), a candidate environmental obesogen, affects lipid metabolism and adipogenesis. Perinatal exposure to DEHP may be associated with metabolic disorders of dams and offspring. The aim of the present study was to explore the effects of exposure of pregnant dams to DEHP on the metabolism and fat distribution of their offspring, and to determine the mechanisms for these effects. Pregnant C57BL/6J mice were administered DEHP via gavage (0.05 or 500 mg/kg/day) from gestational days 1–19. Pups were sacrificed at nine weeks of age. Serum leptin, insulin, lipid and fasting glucose levels, and the weights of the inguinal (subcutaneous) and gonadal (visceral) fat pads were determined. mRNA expression levels of two developmental genes, T-box 15 (Tbx15) and glypican 4 (Gpc4) were detected in fat tissues. A 100% abortion rate was exhibited in 500 mg/kg DEHP-treated dams, whereas exposure to 0.05 mg/kg DEHP did not affect reproductive outcomes. Pups from the 0.05 mg/kg exposure group were used for subsequent experimentation. Serum leptin, insulin, lipid and fasting glucose concentrations in these pups were significantly higher than those of control pups (P<0.05). Although no significant change in body weight was detected, the visceral fat weights of DEHP-exposed pups were significantly higher than those of control pups (P<0.05). Compared with controls, mRNA expression levels of Tbx15 in subcutaneous fat and Gpc4 in visceral fat were significantly increased among DEHP-exposed pups (P<0.01). The present results suggest that in utero exposure to an environmentally safe dose of DEHP may lead to excessive visceral fat accumulation and metabolic disorders in offspring and that aberrant expression of Tbx15 and Gpc4 may have an important role in these effects.